(untitled) (Scientific journal of the Fergana State University, 2024)
It consists of studying the types of eco-tourism resources in the Fergana region, identifying its natural and geographical aspects, and assessing their suitability for ecotourism. When implementing this scientific research, qualimetric analysis, complex natural-geographical, observational, comparative-ecological, cartographic, statistical, systematic analysis, quantitative analysis of natural components, GIS, and other methods are used. The concept of ecotourism and the experience of countries around the world were studied, the possibilities of ecotourism in the Fergana region were analyzed, and ecotourism resources in the Fergana region were assessed and mapped. Tourism is the most effective way to meet the recreational needs of society. Ecotourism and its development are explained by the desire of people, cut off from nature and often deprived of a favorable ecological environment, to communicate with nature, get acquainted with the cultural traditions of other peoples, and receive aesthetic pleasure from rich landscapes. In our country and abroad, there are many definitions of the concept of “ecotourism”, the most concise is the following definition: “Ecotourism is a type of tourism associated with nature and promoting the conservation of ecosystems, taking into account the interests of local people.” In recent years, ecotourism has been expanding in Uzbekistan. The largest and most unique tourist and recreational potential of our country requires scientific and targeted use. This largely applies to our country, because forests lakes, and beautiful natural landscapes have been preserved here, and there are unique natural and cultural heritage sites that are very pleasant for tourists. Given the public interest in ecotourism, the problems of theoretical and methodological aspects of assessing the suitability of a territory for the development of this ecotourism activity have not yet been developed. The authors of scientific works on this issue recommend the following methods as the most suitable for assessing the eco-tourism potential of a territory: a qualitative approach using expert assessment, a scoring method, a sociological survey, and a cartographic method. In the assessment process, it is necessary to take into account factors of various forms that influence leisure activities to varying degrees. Accordingly, it is necessary to consider the overall comprehensive eco-tourism potential of the territory from a factorial point of view.